Sexual Victimization and Official Reporting Behaviors Among Incarcerated Women - Butler, H. Daniel (Victims & offenders, 2025)
Sexual victimization within confinement facilities is difficult to empirically assess for a variety of reasons that include fear of reporting, distrust of correctional staff, and concerns that no action will be taken to prevent subsequent assaults. Given these concerns, there are few assessments of the decisions that influence individuals’ willingness to make an official report to correctional staff. In this study, we use the National Inmate Survey, 2011–2012, a nationally representative sample of incarcerated individuals to understand the reporting behaviors of incarcerated women who are victims of sexual assault. We use the ecological perspective to understand the incident- and individual-factors that influence victims’ reporting behaviors. An examination of reporting behaviors among incarcerated women is particularly salient as this population has unique pathways into the criminal justice system and lived experiences that may influence reporting decisions (e.g. histories of physical or sexual abuse). We conclude with a discussion of theory and policy implications that include the need for better data collection, such as capturing system-responses and prevention strategies.